Final frontier : the pioneering science and technology of exploring the universe - Clegg, Brian (St. Martin's Press, 2014)
"Human beings are natural explorers, and nowhere is this frontier spirit stronger than in the United States of America. It almost defines the character of the US. But the Earth is running out of frontiers fast. Star Trek was right -- there is only one final frontier, and that is space. In Brian Clegg's The Final Frontier we discover the massive challenges that face explorers, both human and robotic, to uncover the current and future technologies that could take us out into the galaxy and take a voyage of discovery where no one has gone before... but one day someone will. In 2003, General Wesley Clark set the nation a challenge to produce the technology that would enable new pioneers to explore the galaxy. That challenge is tough -- the greatest we've ever faced. But taking on the final frontier does not have to be a fantasy.In a time of recession, escapism is always popular -- and what greater escape from the everyday can there be than the chance of leaving Earth's bounds and exploring the universe? With a rich popular culture heritage in science fiction movies, books and TV shows, this is a subject that entertains and informs in equal measure"--